Pengaruh Investasi (PMDN), Angkatan Kerja, Pengeluaran Pemerintah dan Pendidikan Terhadap Pertumbuhan Ekonomi di Indonesia - Mia Fadillah; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
The purpose of this research is to figure out (1) The Influence of investment to the growth economic in Indonesia (2) The Influence of the quantity of workforce, to the growth economic in Indonesia (3) The Influence of goverment expenditure to the growth economic in Indonesia (4) The Influence of education to the growth economic in Indonesia (5) The Influence of investment, the  workforce, goverment expenditure and education to the growth economic in Indonesia. This research uses panel data from 2010-2019, the method is multiple linear regression. the research shows The estimation multiple linear regression (OLS) with the Fixed Effect Model that shows: (1) investment  had an possetive significant influence  to the growth economic in Indonesia(2) the  workforce had an possetive significant influence  to the growth economic in Indonesia (3) goverment expenditure had an possetive significant influence  to the growth economic in Indonesia (4) education had a negative significant influence  to the growth economic in Indonesia. Based on this research the writer suggests to increase the quality of investment, the  workforce , goverment expenditure and education. The government should cooperate strongly with tne participant countries and take action to increase the productivity and the quality of the human sources also increase the investment that makes increase the growth economic in Indoneisa.